Reality, Expectations And Policy Of Madrasah Management In The Era Of Regional Autonomy - Ahmad Zarkasyi (Southeast Asian Journal of Islamic Education Management, 2021)
Abstract The existence of madrasas cannot be separated from Muslims' initial goals and needs for the importance of education. However, the chaotic legal basis also causes the management of madrasas that are not optimal. Education Statistics Data from the Ministry of Education and Culture and EMIS data from the Ministry of Religion of the Republic of Indonesia in 2015 showed the number of madrasas was 76,583 or around 21.31% of the existing schools. By analyzing madrasas, opportunities will be obtained, especially in the era of regional autonomy, and strategies to produce policies intended to strengthen the role and function of madrasas for the community.   Keywords : madrasah, education policy, regional autonomy